The Role of Control of Corruption and Quality of Governance in ASEAN: Evidence from DOLS and FMOLS Test - Pius Lustrilanang; Suwarno; Darusalam; Lutfi Trisandi Rizki; Normah Omar; Jamaliah Said (Cogent Business & Management, 2023)
Corruption is a serious problem in some ASEAN countries except Singapore and Brunei, judging from their ranking and scores on Transparency International's Corruption Perceptions Index (CPI). The concept of good governance is much broader than control of corruption. Governance and corruption may be related, but they are distinct nations and should not be regarded as the same. However, this study's objective is to investigate the nexus between control of corruption and quality of governance from 1984 to 2021 for eight ASEAN countries. Fully Modified Ordinary Least Square (FMOLS) and Dynamic Ordinary Least Square (DOLS) methodologies were used to estimate the long- and short-run relationships. The result reveals a positive and significant relationship between control of corruption and governance quality in ASEAN countries. It means better anti-corruption leads to enhancing the quality of governance in the ASEAN countries. In addition, the relationship between governance quality and control of corruption is also positive and significant. It shows that better governance quality will reduce corruption in the ASEAN region. This study's practical contribution is strengthening its governance and control of corruption in the ASEAN member country's leader. This study's scientific contribution investigated the vice-versa of the relationship between control of corruption and quality of governance, especially in the context of the ASEAN region.
Keywords: 650; ASEAN region; control of corruption; DOLS; FMOLS; guality of governance